The Influence of Interest Rates, Credit Procedures, and Ease of Access on Retirees’ Interest in Applying for Loans at PT. Bank Pembangunan Daerah Jawa Barat dan Banten (Persero) Tbk, Buah Batu Branch Office - Tiara Elanda Suryani; Arie Hendra Saputro (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research is intended to determine the effect of interest rates, credit procedures and ease of access on retirees' interest in applying for credit at PT. Regional Development Bank of West Java and Banten (Persero) Tbk. Buah Batu Branch Office. Data was collected using a quantitative approach with explanatory research type, namely data that has been published previously in various scientific journals and relevant research sources. This study shows that each instrument used has high validity and consistency. Based on the validity test, each item in the Interest Rate (X1), Credit Procedure (X2), Ease of Access (X3), and Interest in Applying for Credit (Y) variables has a Pearson Correlation value greater than the critical value (r table = 0.3044), so that all question items are proven valid for measuring each variable.